2009
DOI: 10.4076/1752-1947-3-7267
|View full text |Cite
|
Sign up to set email alerts
|

Management dilemma of a recurrent huge fibrosarcoma in a 25-year-old African: a case report

Abstract: IntroductionSoft tissue sarcomas are rare tumours that are infrequently seen in most surgical practices. They can occur in any anatomic region of the body. The size of a soft tissue sarcoma is an important prognostic variable and so affects the quality of tumour resection.Case presentationA 25-year-old Nigerian African presented with recurrent huge fibrosarcoma measuring about 55 × 40 × 10 cm at his posterior trunk. The patient's clinical condition was poor; the tumour seemed unresectable and the patient looke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A number of authors have reported excellent outcomes following surgical palliation, even in the presence of metastases, without significant cost, in well selected patients [ 12 , 13 ]. Other reports have indicated patient benefit from wide resection of tumor, with immediate reconstruction, even in the face of positive margins, and/or potential lack of access to adjunct oncologic treatment [ 14 , 15 ].…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors have reported excellent outcomes following surgical palliation, even in the presence of metastases, without significant cost, in well selected patients [ 12 , 13 ]. Other reports have indicated patient benefit from wide resection of tumor, with immediate reconstruction, even in the face of positive margins, and/or potential lack of access to adjunct oncologic treatment [ 14 , 15 ].…”
Section: Definitionsmentioning
confidence: 99%
“…There are not many reports in literature on palliative surgical procedures and even fewer written from the perspective of a resource-constrained environment; most are case reports [ 15 , 18 – 22 ]. Even workers from HICs well appreciate the difficulties in the care of the palliative surgical patient [ 23 ].…”
Section: Definitionsmentioning
confidence: 99%